The Interplay of English as a Foreign Language Learners’ Interest, Self-Efficacy, and Involvement - Liu, Zhengyuan (Frontiers in psychology, 2022)
Founded on the advent of Positive Psychology in recent decades, the learners’ involvement has been a critical issue since the origin of teaching and learning despite it being quickly developed in previous decades. The enhancement of motivational aspects like self-efficacy and interest appears to have a high impact on learners’ success and achievement. Although both constructs are extensively investigated in various subjects, their association between and the learners’ involvement in the process of language learning have not been taken into account so far. This review intended to scrutinize the association among students’ self-efficacy, their academic interest, and their involvement. It is significant to pinpoint that the current review can help educational administrations, professional improvement centers, and policymakers to consider the above-mentioned issues in the progression of language education to develop their involvement.